Efficacy of Some Packages of Fungicide for Seed Treatment and Spraying Corn in the Fields against Downy Mildew - Ichwanul Malik Siregar; Salim Widono; Mohammed Iqbal Faruk; Supyani Supyani (Agrotechnology Research Journal, 2024)
This study aimed to identify the most effective combination of seed treatments and fungicide applications to control downy mildew on corn seeds. It also evaluated the efficacy of various fungicides in suppressing the spread of downy mildew. The research was conducted from October 2021 to January 2022 in Banggle Village, Kanigoro District, Blitar Regency, Central Java Province. The methodology employed a randomized complete block design, with treatment factors including seed treatment and fungicide spraying. Four treatment packages were utilized: one control group with no seed treatment or fungicide application and three others as comparators. Each treatment was replicated four times. The active ingredients used for seed treatment and field spraying included Dimethomorph, Pyraclostrobin, Oxathiapiprolin, and Fenamidone. The results indicated that downy mildew on corn emerged during the fourth week after planting. Corn treated with the fungicide packages exhibited significantly better outcomes compared to the control group. The most effective treatment package involved seed treatment with Dimethomorph and Pyraclostrobin, followed by spraying with Dimethomorph on the seventh day after planting, Oxathiapiprolin on the fourteenth day, and Dimethomorph once again on the twenty-first day after planting. This combination achieved the highest efficacy index of 70.67%.